"Let's All Do the Poznań": Manchester versus Poland both on and off the Pitch - Newsham, Paul (My University, 2025)
The story of the Manchester football clubs’ encounters with Poland begins in 1968 with Manchester United facing Górnik Zabrze in the quarter final of their ultimately successful European Cup campaign and ends with Manchester City fans learning to “do the Poznań” in a 2010 UEFA Europa League group match. This article will discuss those encounters which took place during the Cold War and its immediate aftermath from the perspectives of the players, fans and officials involved. During this period, matches between Manchester and Polish clubs were trips into the unknown, whether that meant crossing the Iron Curtain in the 1960s, 1970s and 1980s, the first and until very recently the only experience of a major European final for both Manchester City and Górnik Zabrze in 1970, or the first away days in Europe for English fans after a five-year ban, in 1991. The aim of the article is to show how sport, and particularly the travelling and crossing of borders involved in international competition, can affect our attitudes towards and opinions on formerly unknown, sometimes mysterious places. This process appears to be largely positive and the article will also propose that the experiences involved with Manchester football clubs meeting Polish opponents are examples of sport as cultural diplomacy, in other words, football diplomacy. The sources consulted will include Polish and English newspaper reports as well as first-hand accounts of players, fans and officials travelling in both directions.
Keywords: Manchester United; Manchester City; Górnik Zabrze; Widzew Łódź; Legia Warszawa / Legia Warsaw; Lech Poznań; football history; cultural diplomacy; football diplomacy; Cold War